SLAVERY ERA TO SOFTWARE ERA: A GRAPH OF AMERICAN CONDITION IN COLSON WHITEHEAD'S APEX HIDES THE HURT - Maruthupandian, P.; Ajith, R. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Contrary to the history books prescribed in school and the well-researched books for public consumption, a great number of people may strongly believe in a different version of the events. People believe so when credit is denied to someone to enhance the role of others. It’s not repeating a lie often to make it a truth but leaving out some people’s contribution to over glorify somebody else’s contribution. This research paper attempts to find how people in power have tweaked the memories of their contemporaries and created a narrative of events that took generations to change.